2014
DOI: 10.1111/acem.12327
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Admit Wait Times: The Effect of a Leadership‐based Program

Abstract: Objectives: Prolonged admit wait times in the emergency department (ED) for patients who require hospitalization lead to increased boarding time in the ED, a significant cause of ED congestion. This is associated with decreased quality of care, higher morbidity and mortality, decreased patient satisfaction, increased costs for care, ambulance diversion, higher numbers of patients who leave without being seen (LWBS), and delayed care with longer lengths of stay (LOS) for other ED patients. The objective was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 44 publications
(61 reference statements)
0
31
0
1
Order By: Relevance
“…This research focus on stakeholders and situations that fall within the purview and authority of DEMs is also reflected in studies of the organisational impact of DEMs. To date, research has examined the impact of EM leadership on clinical quality, efficiency, responsiveness, admit wait‐times and lengths‐of‐stay, cardiac arrest team effectiveness, unit performance and employee satisfaction . Little has been documented about the impact of DEMs beyond the ED.…”
Section: Introductionmentioning
confidence: 99%
“…This research focus on stakeholders and situations that fall within the purview and authority of DEMs is also reflected in studies of the organisational impact of DEMs. To date, research has examined the impact of EM leadership on clinical quality, efficiency, responsiveness, admit wait‐times and lengths‐of‐stay, cardiac arrest team effectiveness, unit performance and employee satisfaction . Little has been documented about the impact of DEMs beyond the ED.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, some EDs have shown that these core issues can be productively addressed in ways that improve both patient care and patient satisfaction. For instance, EDs have improved satisfaction by proactively communicating with patients about wait time,7 incorporating Lean manufacturing principles,8 and working with hospital leadership to reduce boarding 9…”
mentioning
confidence: 99%
“…3 We found significant improvements in admit wait times, boarding time per admission, LOS, patient satisfaction, LWBS, and ambulance diversion hours. Interestingly, during the period of study, we actually reduced physical bed capacity at this ED from 45 beds down to 36 beds.…”
mentioning
confidence: 64%